Evaluation of Using Information Technology in STD Bali with ISO 20000 and COBIT5 Framework - Murpratiwi, Santi Ika; Gustina, Angelina Widya; Dewi, Indah Cahya (International Journal of Engineering and Emerging Technology; Vol 1 No 1 (2016): July - December, 2017)
The development and the use of information technology increased significantly must be balanced with the evaluation process to determine the standardization of technologies that are already running so it can be used as a reference for the future policy formulation. One way to evaluate is to audit. In this study, to discuss the evaluation of using information technology at the College of Design (STD) Bali. It s objective is to conduct an audit for using information technology in accordance with the standards of ISO 20000 and COBIT 5 framework . In ISO 20000 framework, the focus is on the process while in the Service Management Process meanwhile COBIT 5 framework is focused on the evaluation domain, likes Evaluate , Direct, and Monitor (EDM). When do the audit, the process begins with the collection of data through interviews and questionnaires with sources that have been determined in accordance with the domain and control objectives are consists students, faculty, and staff of STD Bali. Furthermore, in the process of data analysis, conducted several stages of the domain determination, determination of process control, determination of indicators, and the mapping of the level of maturity (maturity level). The conclusion of the process of evaluation of using information technology in STD Bali is on level 3, it defined where STD Bali application of information technology has done well and is already prevalent in all fields.